Jewish Libya : Memory and Identity in Text and Image - Roumani, Judith; Meghnagi, David; Roumani, Jacques (Book collections on Project MUSE., 2018)
This anthology brings together the work of a range of distinguished scholars to provide a contextual understanding of Jewish Libya. In highlighting important aspects of this now-fragmented culture and society, this collections seeks to commemorate, celebrate, and preserve vital elements of the Libyan Jewish heritage and evoke an inter-generational exchange among the 200,000 Jews of Libyan origin worldwide.